Effects of Digital Economy on Factor Market Distortion in China: A Spatial Econometric Approach - Xiang, Yun; Lyu, Yanfang; Wang, Dong (Journal of advanced computational intelligence and intelligent informatics, 2024)
Factor market distortion hinders economic growth, and digital economy may provide an impetus to help alleviate the misallocation. Based on China’s provincial panel data from 2013 to 2021, this study applies a dynamic evaluation method to measure the comprehensive level of digital economy, and constructs a spatial econometric model to investigate its impacts on factor market distortion, as well as the differences before and during the COVID-19 pandemic. The empirical findings indicate that China’s digital economy development shows a steady upward trend at the provincial level, has a spatial spillover effect on factor market distortion, and plays a dissipating role, which embodies the potential of digital economy in improving the optimal allocation of resources. At the same time, there is a phenomenon of unbalanced digital economy development in different areas, reflecting the “digital divide” problem. Moreover, during the COVID-19 pandemic, various mobility restrictions were launched, which promotes continuous penetration of the digital economy in various fields of the economy, and its effects on alleviating the factor market distortion are manifested. Overall, this study provides some enlightenments to better implement digitalization strategies.